Celastrol as a potential phytopharmaceutical for medulloblastoma therapy: Assessing efficacy and cardiotoxicity - Alvina Imran (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Cancer remains a pervasive global health challenge associated with substantial mortality. While current chemotherapy treatments are efficacious, they frequently entail significant off-target effects, notably hepatotoxicity, neurotoxicity, and cardiotoxicity, impacting long-term patient survival. Childhood cancers, including medulloblastoma, present additional complexities due to the heightened susceptibility of these individuals to these off-target effects3. Thus, a compelling need exists to evaluate novel therapeutics with heightened efficacy and diminished off-target effects. This article has been reviewed by Dr Matthew Jones, Lecturer in Biomedicine (Physiology), University of Salford. The Editorial Team would like to thank him for his time and contributions.